Controlled droplet transport on a gradient adhesion surface. Issue 27 (5th March 2015) - Feng, Shile; Wang, Sijie; Liu, Chengcheng; Zheng, Yongmei; Hou, Yongping
Abstract : A surface with continuously changed adhesion from ultrahigh to ultralow is fabricated by an integrated method of anodic oxidation combined with octafluorocyclobutane (C4 F8 ) plasma. Abstract : A surface with continuously changed adhesion from ultrahigh to ultralow is fabricated by an integrated method of anodic oxidation combined with octafluorocyclobutane (C4 F8 ) plasma. The control of droplet transport along the direction of the adhesion gradient in length is achieved, as the surface is submitted to either tilted angle or vibration frequency.